Ultrasound-guided thoracic paravertebral block combined with dexmedetomidine improves perioperative analgesia and recovery in medical thoracoscopy: a randomized controlled trial - Nie, Jia; Chen, Wei; Ma, Huanhuan; Fang, Liang; Deng, Zhimin; Zhang, Yu; Wang, Hai-Ying (Frontiers in Pharmacology, 2025)
BackgroundMedical thoracoscopy (MT) is increasingly performed under local anesthesia with sedation, yet suboptimal analgesia and discomfort remain common and may compromise patient safety, cooperation, and recovery. Ultrasound-guided thoracic paravertebral block (TPVB) provides targeted, long-lasting analgesia, while dexmedetomidine offers cooperative sedation with minimal respiratory depression. Evidence for their combined use in MT is limited. This study evaluated the perioperative efficacy and safety of TPVB plus dexmedetomidine compared with conventional local anesthesia and sedation.MethodsIn this prospective, randomized, controlled single-center trial, 83 patients undergoing elective MT were allocated to receive either TPVB plus intravenous dexmedetomidine sedation (Nerve Block group, n = 41) or standard local infiltration with conventional sedation (Control group, n = 42). Primary endpoints were intra- and postoperative pain scores (Visual Analog Scale [VAS], Behavioral Pain Scale [BPS]) and sedation depth (Bispectral Index [BIS]). Secondary endpoints included Quality of Recovery-15 (QoR-15) score at 24 h, intraoperative physiological stability, drug consumption, adverse events, and other recovery indicators.ResultsBaseline characteristics were comparable between groups. TPVB plus dexmedetomidine provided significantly lower intraoperative VAS and BPS scores across all major procedural stages (all P < 0.05) and reduced postoperative VAS at 1 h, 6 h, and 24 h (all P < 0.05) without rebound pain. BIS values remained within the target range in both groups, with no differences (P > 0.05). The Nerve Block group achieved markedly higher QoR-15 scores at 24 h (median [IQR] 136.0 [124.0–137.5] vs. 127.0 [124.0–129.5]; P < 0.001), exceeding the minimal clinically important difference. Intraoperative hemodynamics, oxygenation, sedative and analgesic drug requirements, and the incidence of hypotension, bradycardia, hypoxemia, or movement were similar between groups, with no major cardiopulmonary or block-related complications. Other recovery outcomes (time to ambulation, gastrointestinal recovery, length of stay, PONV incidence) were comparable.ConclusionIn patients undergoing MT, ultrasound-guided TPVB combined with dexmedetomidine sedation significantly improved perioperative analgesia and early postoperative quality of recovery without increasing adverse events. This multimodal approach offers a safe, patient-centered anesthetic strategy aligned with enhanced recovery principles and may represent a preferred regimen for MT and other minimally invasive pleural interventions.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2500098034.